DEVELOPMENT OF INNOVATIVE LEADERSHIP POTENTIAL IN EDUCATION SYSTEM - A. Y. Ogorodnikov (Образование и наука)
The aim of the research is to reveal the educational formation mechanisms of manager personality, including the ability to operate the intellectual capital at all levels of activities, to disclose innovative competence in dealingwith special problems as the regulation of social and organizational processes, to apply knowledge on the management factors efficiency, human needs, attitudes, and modern management techniques. Methods. The research outcomes include the methods of social control organization in the innovation sphere, based on the design of the value system that integrates the intellectual activities of employees into a unified semantic informational space, which promotes the socio-cultural development of various social groups and institutions. Sociological methods of the expert survey in the form of in-depth interviews are applied as an empirical basis of the present study. Cognitive modeling method is used in the course of interpretation and data analysis. The author draws the conclusion using the method of dialectical opposition unity. Results. The research findings demonstrate the characteristics of managers who are good at effective mobilizing the intellectual resources while encouraging the staff members’ capabilities of self-development and self-training. The article deals with the integral indicators of management entity engagement including the arrangement of conditions and interaction system that sustain innovative values updating in some organizations in order to improve organization efficiency in accordance with the stated objectives.Scientific novelty. The author summarizes the theoretical basis of modern means and methods of social institutions management, including educational institutions. General management mechanisms of innovative leadership potential realization are presented in the form of the hierarchic unity. It is shown that intellectualcapital integration into innovative processes of an organization ought to include the creation of an integration system of human, national and organizational values. Intellectual capital is considered as the main subject to management. The author insists on the succession principles observance analyzing the management theories of various intellectual assets and its process of transformations. It is specially noted that the integration of management models based on innovation, and classical resources, allows the development of social controlmethods to minimize the risk in the face of uncertainty, forward the sustainable development of the organization, able to adapt not only dynamic, but also a stable environment. Practical significance. The research outcomes can be used for further development of management training techniques involved in the innovation process, as well as by the managers to improve the methods of updating the intellectual capital of the organization, including educational institutions.